CURRICULAR INTEGRATION AS A STRATEGY TO STRENGTHEN THE EDUCATIONAL PROCESS IN PUBLIC INSTITUTIONS IN COVID-19 TIMES - Bahamón, Magda; Cruz, Paola; Campillo, Diego (Revista Inclusiones, 2021)
This document intends to inform the reflective process that the teachers at the Jorge Eliécer Gaitán High School in Florencia, Caquetá, have had as a solution to the impact that the COVID-19 pandemic has left on public education. First, it addresses the problem identified in school in terms of applied teaching methodology and the need to change it to improve student motivation and learning in the midst of the pandemic. Then, it shows the methodology proposed and applied by the teachers in the school. Finally, it highlights the effects that the methodology has had on the perceptions of teachers and students on the teaching and learning process.